2021
DOI: 10.1155/2021/7497346
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-Androgenic Steroid Misuse: Mechanisms, Patterns of Misuse, User Typology, and Adverse Effects

Abstract: Anabolic-androgenic steroids (AAS) encompass a broad group of natural and synthetic androgens. AAS misuse is highly prevalent on a global scale, with the lifetime prevalence of AAS misuse in males being estimated to be around 6%, with 15 to 25% of male gym attendees using it at any one time. AAS are associated with sudden cardiac death, neuropsychiatric manifestations, and infertility. The average AAS user is unlikely to voluntarily declare their usage to a physician, with around 1 in 10 actively engaging in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Lifetime prevalence of AAS use in males is estimated to be 2% to 6%. 94,95 AASs may increase cardiovascular risk though many mechanisms, including through adverse cardiac remodelling, leading to diastolic dysfunction and sudden arrhythmic death. 96,97 In this review, we focus on vascular effects that The underlying pathophysiology and vascular sequelae are very similar to those of cocaine use, with some important differences.…”
Section: Anabolic Androgenic Steroidsmentioning
confidence: 99%
“…Lifetime prevalence of AAS use in males is estimated to be 2% to 6%. 94,95 AASs may increase cardiovascular risk though many mechanisms, including through adverse cardiac remodelling, leading to diastolic dysfunction and sudden arrhythmic death. 96,97 In this review, we focus on vascular effects that The underlying pathophysiology and vascular sequelae are very similar to those of cocaine use, with some important differences.…”
Section: Anabolic Androgenic Steroidsmentioning
confidence: 99%
“…23 The difference in the results of these two studies can be attributed to the differences in the type of steroid, so as mentioned before, liver enzymes exposed to stanozolol are in the front line of change and damage. 4 The results showed that TT consumption at doses of 50 and 100 mg/kg reduced AST, ALT, and ALP levels in rats exposed to stanozolol. Besides, the effect of the 100 mg/kg dose on reducing AST and ALP levels was far better than the effect of the 50 mg/kg dose.…”
Section: Discussionmentioning
confidence: 94%
“…In other words, approximately 33%-66% of mortality cases are due to these complications, with the remaining being caused by liver failure and liver cancer. 4 Oral 17-α alkylated androgens such as methyltestosterone, nandrolone, oxandrolone, and stanozolol (S) disrupt the process of absorption and clearance of the liver and disturb liver enzymes 5 . In this vein, hypoglycemia, insulin resistance, and dysfunction of the enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were observed in athletes who reported AAS abuse in a survey.…”
mentioning
confidence: 99%
“…Estrogen: The results of current study showed a significant increase in the estrogen level in the treated animals compared to the control group animals. The reason for this rise may be attributed to Dianabol, which was dosed to the two treatment groups, as it contains in its chemical composition (c-alpha-methyl), so Dianabol is one of the androgens that can produce estrogen in high proportions by aromatase enzyme or The so-called cytochrome p450, As this enzyme can catalyze the oxidation reaction of the structural androgen Dianabol, the carbon atoms (c1-2) and (c-alpha-methyl) are oxidized to be turning part of it into (17-β-estradiol), which is the most effective form of estrogen (18).…”
Section: Discussionmentioning
confidence: 99%
“…animals of experiment: In our experiment, we used 30 adult male rabbits, their weights (1600-2100) grams, age (16)(17)(18)(19)) months, a room was equipped with a large air window, cages made of iron clips with dimensions (95 cm x 70 cm x 65 cm) were used, In each cage, five randomly distributed animals were placed in it , the room temperature was (24-28)c. Androgen anabolic (Dianabol): Dianabol tabs 5mg manufactured by the British company (BIOSAFE) was purchased from a bodybuilding gym, tabs are ground into a fine powder to make an easy orally dose suspension.…”
Section: Methodsmentioning
confidence: 99%